Knowledge and Perceptions of Corona Virus Disease (COVID 19) among Nurses Working at Teaching Hospital, Banke, Nepal - Acharya, Sunita; Giri, Shanti; Panth, Asha (Journal of Advanced Academic Research, 2023)
Background Coronavirus Disease (COVID-19) is an infectious, pandemic disease affecting many countries globally. The outbreak of a new virus occurred in Wuhan, China, in December 2019. The objective of the study was to find out the knowledge and perceptions of nurses on COVID-19 in a teaching hospital, Banke, Nepal. A quantity web-based cross-sectional survey was conducted at Nepalgunj Medical College, Teaching Hospital, Kohalpur Banke, which was selected purposively. All the nurses working in different departments who agreed to participate in the study were included in the study. A self-administered questionnaire in google form was developed by the researchers Data were analyzed by using descriptive and inferential statistics. Results The study shows that more than half (56%) of the nurses had an adequate level of knowledge and the majority (97%) of nurses had a satisfactory perception regarding COVID-19. There was a statistically significant association between the age of the nurses with the level of knowledge regarding COVID-19 (P=0.009). Those nurses who were up to 25 years had 3.166 times inadequate knowledge than those above 25 years (p=0.009; OR= 3.166; CI=1.315-7.621). There was no statistically significant association between socio-demographic characteristics with the perception of nurses regarding COVID-19. Conclusion The findings conclude that more than half of the nurses had an adequate level of knowledge regarding COVID-19 and the majority of nurses had satisfactory perception regarding COVID-19. The global threat of COVID-19 continues to emerge, it is critical for improving the knowledge and perceptions of the nurses in this pandemic situation.